A Novel Travelling Time Estimation Mechanism for Minimizing Unnecessary Handovers from Cellular Networks to WLANs - Mahmood, Adnan; Zen, H.; Othman, A.K.; Siddiqui, S.A. (IEEE, 2014)
The ‘Beyond 3G Wireless Networks Architecture’ proposes to assimilate numerous heterogeneous wireless network technologies over an Internet Protocol Backbone. However, in order to offer seamless mobility, cost - effective connectivity and desired Quality of Service (QoS) in such a diverse environment; efficacious vertical handover support still remains a major design challenge. In this research/manuscript, a novel handover decision mechanism, ‘Travelling Time Prediction Based on the Consecutive RSS Measurements’ in an IEEE 802.11 WLAN cell is suggested. The method uses a time threshold which is computed by a Mobile Terminal (MT) as soon as it penetrates into a WLAN boundary. The estimated travelling time is then compared with the time threshold, so as to make handover decisions for minimizing the probability of unnecessary handovers. Our performance analysis reveals that the suggested mechanism effectively reduces number of unnecessary handovers by 60% as compared to the already proposed schemes.